Numerical solution of a model for brain cancer progression after therapy - Jackiewicz, Zdzislaw; Kuang, Yang; Thalhauser, Craig; Zubik-Kowal, Barbara (Mathematical Modelling and Analysis, 2009)
We present a numerical scheme used to investigate a mathematical model of tumor growth which incorporates multiple disparate timescales. We simulate the model with different initial data. The initial conditions explored herein correspond to a small remnant of tumor tissue left after surgical resection. Our results indicate that tumor regrowth begins at the pre‐surgery tumor‐healthy tissue interface and penetrates back into the original tumor area. This growth is rate‐limited by the reformation of the tumor vascular network. First published online: 14 Oct 2010